Gestão de aspectos ambientais indiretos: uma ferramenta para auditoria de fornecedores de serviços - José Neto, Julio (2012)
The management of environmental issues goes beyond the inner spheres of the company and encompasses the entire network of organizations involved in the process. Since the environmental practices of service providers affect the performance of the organization, the associated economic, social and environmental impacts must not be treated separately, but in a systemic and integrated approach. The aim of this study was to develop an audit tool to evaluate the company service providers. Questionnaires for assessment and self-assessment were developed, using administrative, legal, fiscal, environmental and social criteria, to obtain an environmental performance index. The tool was used to evaluate recyclers for electronic, polymer and cellulosic waste generated in the computer manufacturing process. The assessment included questions related to waste management, atmospheric emissions, water, noise, and legislation compliance and transportation rules. The tool generates an index of the evaluation process, allowing an integrated comparison of the suppliers. The results obtained show unawareness of basic environmental issues, and serve to direct the actions to solve the main problems. The tool is useful to monitor the socio-environmental performance of providers and may also encourage the modification of inappropriate environmental practices in order to help minimize environmental impacts throughout the production chain.